1975
DOI: 10.1007/bf03004868
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative epidural analgesia: Effects on lung volumes

Abstract: FUNCTIONAL RESIDUAL CAPACITY (FRC) is reduced following upper abdominal operations under general anaesthesia. The changes which have been reported <1-5) are summarized in Table I. A number of factors can be responsible for the changes observed.The reduction of FRC which follows induction of general anaesthesia may persist. The cause for this reduction is still undetermined, but the fall is not progressive with time and is related to body size. (6,7) Loss of lung volume by atelectasis or oedema will reduce FRC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
3

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(23 citation statements)
references
References 28 publications
0
20
0
3
Order By: Relevance
“…In fact, thoracic epidural anesthesia leads to an improvement of lung function. In 1975, Whaba et al [28] demonstrated that the reduction in functional residual capacity (FRC) improved from 21.7% to 15.9%, and the reduction in VC improved from 63% to only 45% when epidural anesthesia was used following upper abdominal surgery. Thirteen years later, Mankikian et al [29] used epidural anesthesia in patients who underwent abdominal aortic surgery with a complete longitudinal abdominal incision, and demonstrated an improvement in VC from 1380 ± 115 ml to 1930 ± 144 ml.…”
Section: Postoperative Analgesia and Lung Functionmentioning
confidence: 97%
“…In fact, thoracic epidural anesthesia leads to an improvement of lung function. In 1975, Whaba et al [28] demonstrated that the reduction in functional residual capacity (FRC) improved from 21.7% to 15.9%, and the reduction in VC improved from 63% to only 45% when epidural anesthesia was used following upper abdominal surgery. Thirteen years later, Mankikian et al [29] used epidural anesthesia in patients who underwent abdominal aortic surgery with a complete longitudinal abdominal incision, and demonstrated an improvement in VC from 1380 ± 115 ml to 1930 ± 144 ml.…”
Section: Postoperative Analgesia and Lung Functionmentioning
confidence: 97%
“…10 Despite the short duration of epidural analgesia, the subjective group did not suffer any increase of pain and also showed a higher postoperative VC and 6MWD than the control group. Therefore, the decrease in the postoperative impairment of 6MWD and VC in the subjective group should not be influenced by postoperative pain.…”
Section: Discussionmentioning
confidence: 95%
“…As postoperative pain was accepted as a major factor [15,16], pulmonary restrictive effect was independent of pain. Several studies demonstrated that anesthetic wound infiltration and intercostal nerve blocks do not completely prevent the restrictive defect after abdominal surgery [15,[17][18][19]. Rademaker et al [20] provides adequate pain relief by extradural analgesia after laparoscopic cholecystectomy, but did not observe improvement in lung dysfunction Although Peters et al [21] has underlined residual pneumoperitoneum as a factor of impaired diaphragmatic function after laparoscopic cholecystectomy, carbon dioxide pneumoperitoneum alone, such as for diagnostic laparoscopy, does not impair diaphragmatic function [22].…”
Section: Discussionmentioning
confidence: 99%